Psychological Counseling among University Students Worldwide: A Systematic Review - Silvia Cerolini; Andrea Zagaria; Costanza Franchini; Vito Giuseppe Maniaci; Alexandro Fortunato; Chiara Petrocchi; Anna Maria Speranza; Caterina Lombardo (MDPI AG, 2023)
University counseling services (UCSs) are actively involved in mental health assessment and in supplying interventions aimed at preventing, facing and possibly overcoming psychological problems. However, we do not have a global overview of psychological counseling among universities. This systematic review aims at reviewing the literature on university psychological counseling, including articles documenting: (1) mental health and attitudes regarding help-seeking behaviors and UCSs among university students or counselors, (2) the description of protocols/services among UCSs, (3) the efficacy of psychological counseling/interventions among university students (both face-to-face and internet-delivered interventions). The study followed PRISMA guidelines and was registered on PROSPERO. After defining inclusion and exclusion criteria, a literature search was conducted, identifying 7085 records. Finally, 152 articles met the review eligibility criteria and were included in the qualitative synthesis. Results are divided into seven thematic topics that emerged during the analysis of the literature. The results mainly showed that face-to-face and web-based counseling/psychological interventions improve university students' mental health. Cross-sectional studies showed that many biases exist toward help-seeking behaviors, especially among international students. Both students and counselors must strive to overcome cultural barriers. Available resources for UCSs are scarce and need to be strengthened, as well as efficacy studies through randomized clinical trials.